Circular RNA MAT2B promotes migration, invasion and epithelial-mesenchymal transition of non-small cell lung cancer cells by sponging miR-431. Issue 16 (18th August 2021) - Wang, Hui; Feng, Li; Cheng, Deyun; Zheng, Yuqiong; Xie, Yimin; Fu, Bing
ABSTRACT: Circular RNAs (circRNAs) have recently been described as key regulators in the progression of non-small cell lung cancer (NSCLC), and this study aimed to investigate the functional role of circMAT2B in NSCLC. CircMAT2B expression in NSCLC tissues and cell lines was investigated using RT-qPCR analysis. A series of functional experiments, including MTT assay, colony formation assay, wound healing assay and transwell assay, were carried out to investigate the effects of circMAT2B knockdown/overexpression on the malignant traits of NSCLC cells. Western blot analysis was performed to detect the expression of EMT-related proteins. Dual-luciferase reporter assay and RIP assay were further carried out to analyze the interaction between circMAT2B and miR-431 in NSCLC. We observed that circMAT2B was overexpressed in NSCLC tissues and cell lines, and high expression of circMAT2B was closely associated with large tumor size, advanced TNM stage and poor prognosis of NSCLC patients. Further functional experiments showed that circMAT2B knockdown markedly inhibited the proliferation, migration, invasion and EMT of NSCLC cells, whereas circMAT2B overexpression led to the opposing results. Mechanistically, circMAT2B could directly interact with miR-431, and subsequently decrease miR-431 expression in NSCLC. The effects of circMAT2B overexpression in NSCLC cells were abrogated by miR-431 restoration. Our findings revealed the novel oncogenic roles of circMAT2B in NSCLC by sponging miR-431.